Learning to Wait: A Laboratory Investigation - OPREA, RYAN; FRIEDMAN, DANIEL; ANDERSON, STEVEN T. (Review of Economic Studies, 2009)
Human subjects decide when to sink a fixed cost C to seize an irreversible investment opportunity whose value V is governed by Brownian motion. The optimal policy is to invest when V first crosses a threshold V* = (1 + w*)C, where the wait option premium w* depends on drift, volatility, and expiration hazard parameters. Subjects in the Low w* treatment on average invest at values quite close to optimum. Subjects in the two Medium and the High w* treatments invested at values below optimum, but with the predicted ordering, and values approached the optimum by the last block of 20 periods.